PENERAPAN MODEL BRAND EQUITY TEN PADA UPBJJ-UT BOGOR - Surapto, Deni (Jurnal Organisasi dan Manajemen, 2014)
The objectives of the study are to (1) analyze the dimensions of awareness, associations, perceived quality/leadership, loyalty, and market behavior based upon the assessment of Open University students and the public, (2) evaluate the Open University brand equity model based on brand equity ten. The time period of research was during April-July 2012 and the location was in Open University Bogor campus. The population of this study consisted of high school students, employees and students of Open University Bogor, amounting to 693,950 people. Samples of 400 people were obtained. The data is collected using survey method, whereby interviews of the sample group is conducted using a closed form questionnaire based upon the Likert scale method. Based on the results from the analysis of the measures of awareness and brand recall, the Open University got the ranking of 11th and 7th among the other universities from 2% of the respondents respectively. It was ranked 1st on the measure of recognition and unaware by 5.5% of respondents. Based on the results from the analysis of the measure of association using Cochran test, it was found that the attributes of time and cost are associated with the brand of Open University. Results from the analysis of the measure of perceived quality regarding quality of services provided by Open University to its students show that registration services rated good while study material, online tutorials and exams were assessed as fair. Result from the analysis of the price premium loyalty measures indicate that students objected to an increase in tuition over Rp.25.000,-. Satisfaction measure indicates that the level of satisfaction of the Open University students is up to the extent of liking the brand, that is like and enjoy the study at Open University. This is indicated by the highest score received for the level of liking the brand which is 70%. Result from the analysis of the measure market behavior regarding market share shows that market share of Open University is estimated to be 0.24%. Distribution coverage shows that the Open University Bogor has reached up to 89.45%. In conclusion it is found that the brand equity ten index of Open University is 42,36, which indicates that its brand equity is still low and not strong. Tujuan dari penelitian ini adalah untuk (1) menganalisis dimensi kesadaran, asosiasi, persepsi kualitas/kepemimpinan, loyalitas, dan perilaku pasar berdasarkan penilaian mahasiswa Universitas Terbuka dan masyarakat, (2) mengevaluasi merek model ekuitas Universitas Terbuka berdasarkan merek ekuitas sepuluh. Jangka waktu penelitian adalah selama April-Juli 2012 dan lokasi di Universitas Terbuka kampus Bogor. Populasi penelitian ini terdiri dari siswa SMA, karyawan dan mahasiswa Universitas Terbuka Bogor, berjumlah 693.950 orang. Sampel dari 400 orang diperoleh. Data dikumpulkan menggunakan metode survei, dimana wawancara dari kelompok sampel dilakukan dengan menggunakan kuesioner bentuk tertutup berdasarkan metode skalaLikert. Berdasarkan hasil dari analisis tindakan kesadaran dan ingat merek, Universitas Terbuka mendapat peringkat 11 dan ke-7 di antara universitas lain dari 2% dari responden masing-masing. Ini peringkat 1 pada ukuran pengakuan dan menyadari 5,5% responden. Berdasarkan hasil dari analisis ukuran asosiasi menggunakan uji Cochran, ditemukan bahwa atribut waktu dan biaya yang terkait dengan merek Universitas Terbuka. Hasil dari analisis ukuran persepsi kualitas mengenai kualitas layanan yang diberikan oleh Universitas Terbuka untuk mahasiswa menunjukkan bahwa layanan pendaftaran dinilai baik saat materi studi, tutorial online dan ujian dinilai sebagai adil. Hasil dari analisis harga tindakan loyalitas premium menunjukkan bahwa siswa keberatan dengan kenaikan biaya kuliah lebih Rp.25.000,-. Mengukur kepuasan menunjukkan bahwa tingkat kepuasan mahasiswa Universitas Terbuka adalah sampai sejauh mana menyukai merek, yaitu seperti dan menikmati studi di Universitas Terbuka. Hal ini ditunjukkan dengan nilai tertinggi yang diterima untuk tingkat menyukai merek yang 70%. Hasil dari analisis perilaku pasar ukuran mengenai pangsa pasar menunjukkan bahwa pangsa pasar dari Universitas Terbuka diperkirakan 0,24%. Cakupan distribusi menunjukkan bahwa Universitas Terbuka Bogor telah mencapai hingga 89,45%. Dalam kesimpulan ditemukan bahwa indeks ekuitas merek sepuluh dari Universitas Terbuka adalah 42,36, yang menunjukkan bahwa ekuitas mereknya masih rendah dan tidak kuat.